From digit-sucking-cum-deglutition to deglutition in dentate subjects - Fellus, Patrick (Orthodontie française, 2016)
Failure to manage function-related problems can lead to failures in the conduct of orthodontic treatment and to poor stability. However, even if the dysfunctions have been diagnosed by the practitioner, he/she will still be dependent on the quality of the rehabilitation. Traditionally, rehabilitation requires intensive participation on the part of patients in order to ensure stimulation to their cortical neural networks. Eric Kandel, winner of the Nobel Prize for Medicine in 2000, has shown that this approach stimulates information transmission by boosting the activity of the neurotransmittors. Likewise, he demonstrated that when rehabilitation is aimed at the sub-cortical pathway, there is no longer augmentation of the neurotransmission but rather the build-up of new circuits involving the creation of new synapses. Today, it is possible to rehabilitate swallowing and breathing by the sub-cortical pathway.